Behavioral and Cognitive Avoidance as Predictors of Session-by-Session Change During Prolonged Exposure Therapy - Pandey, Shivani (My University, 2026)
Avoidance of trauma-related stimuli and feelings can provide short term relief. However, long-term avoidance can become pervasive, hindering new learning that is necessary for therapeutic change. This study investigated the role of both pre-treatment and in-session measures of behavioral avoidance and rumination, conceptualized as a cognitive avoidance strategy, on PTSD and depression symptom change during a course of prolonged exposure (PE) therapy. We hypothesized that higher pre-treatment and in-session avoidance would be predictive of flatter reductions in both PTSD and depression symptom change from pre-to-post treatment. Data from a randomized control trial (N = 149) were used to investigate study questions. Pre-treatment behavioral avoidance and rumination were measured with self-report measures. Avoidance and unproductive processing, a form of rumination, during PE sessions was measured using an observational coding system (CHANGE). Structural equation models were used to investigate study questions. Contrary to hypotheses, analyses revealed higher pre-treatment behavioral avoidance, but not rumination, was associated with steeper decreases in PTSD symptoms (β = -.373; p = .004) throughout treatment. Higher baseline rumination, but not behavioral avoidance, was associated with steeper decreases in depression symptoms (β = -.221; p = .032) from pre-to-post treatment. Higher in-session avoidance was associated with less declines in PTSD symptom trajectories (β = .327; p = .026). Taken together, individuals with high baseline rumination and avoidance can still make clinically meaningful shifts during PE. Mid-point of treatment seems to be an important time during which therapeutic stagnation may occur, indicating that clinicians should pay special attention to avoidance and emotional engagement at this time to ensure therapeutic gains.
Thesis (Master's)--University of Washington, 2026
Keywords: Clinical psychology; Psychology